ANALISIS AVERAGE ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SETELAH RAMADHAN EFFECT PADA SEKTOR TRANSPORTASI & LOGISTIK - Salma Amanda (2023)
This research is a quantitative study aimed at determining whether there are differences in Average Abnormal return and Trading volume activity in the transportation & logistics sector's stocks before and after the month of Ramadan. In establishing the sample, the total sampling method was employed to select the entire population, consisting of 24 companies continuously listed in the Transportation and Logistics sector on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Hypothesis testing in this study utilized the Wilcoxon Signed-Rank Test data analysis technique and Paired Sample T-Test through the SPSS (Statistical Package for the Social Sciences) version 29. The findings from this observation indicate no difference in the Average Abnormal return variable between the periods before and after Ramadan from 2019 to 2023. However, the research did not identify a significant difference in the Trading volume activity variable between the periods before and after Ramadan within the same timeframe, spanning from 2019 to 2023.